Going beyond the official domain in the search for the culture of employee learning: The case of junior support staff at a South African university - Mavunga, George (Critical Studies in Teaching and Learning, 2023)
Based on HCT (human capital theory), employee learning and the culture associated with it in South Africa and globally have generally been researched from the perspective of the normative government or employer-initiated policies and programmes. Using Bernstein’s (2000) theory of the pedagogic device, this paper suggests the existence of different domains of learning with respect to junior support staff at a South African university. The paper also borrows from critical realism to advocate an approach which asks questions pertaining to the influence of structure and agency on the form of the culture of employee learning in different domains with respect to the junior support staff members. The answers to these questions, the paper suggests, would help with a holistic characterisation of the culture of employee learning associated with this category of employees at the South African university.